Jaring Pengaman Sosial: Analisis Anggaran Penanganan COVID-19 di Aceh - Vellayati Hajad; Ikhsan Ikhsan; Nodi Marefanda (Department of Government Studies, Universitas Syiah Kuala, 2021)
This study discusses the budget for handling COVID-19 in Aceh Province with a Social Safety Net approach. Through this Social Safety Network approach, the Aceh Government has allocated a budget for handling COVID-19 is intended to be given to acehnese people who are directly affected from COVID-19. While the purpose of this study is to find out the extent of the success of the budget for handling COVID-19 is realized to the public to rise from the crisis during the COVID-19 pandemic. This research is an exploratory descriptive qualitative method research to explain and dig up information about the budget for handling COVID-19 by answering various types of questions and problems that occur and are identified and analyzed based on the results of readings and interpretation data related to the research theme. The results showed that the budget for handling COVID-19 in Aceh Province in the Social Safety Net sector was already running and the affected Acehnese people had received social assistance provided by the Aceh Government. However, there needs to be supervision from the people of Aceh in order for transparency in the management of the COVID-19 budget. In addition, in anticipation that the practice of corruption in handling the COVID-19 budget in the Aceh Government environment can be prevented.